Red Dirt Education Leaders ‘Caught in the Middle’: Priorities for Local and Nonlocal Leaders in Remote Schools - Guenther, John; Osborne, Samuel (The Australian Journal of Indigenous Education, 2020)
Schooling for Aboriginal and Torres Strait Islander students in remote or ‘Red Dirt’ communities has been cast as ‘problematic’, and ‘failing’. The solutions to deficit understandings of remote schooling are often presented as simple. But for those who work in Red Dirt schools, the solutions are not simple, and for education leaders positioned between the local Red Dirt school and upward accountability to departments of education, they are complex. Between 2011 and 2016, the Cooperative Research Centre for Remote Economic Participation's (CRC-REP) Remote Education Systems project explored how education could better meet the needs of those living in remote communities. More than 1000 people with interests in remote education contributed to the research. Education leaders were identified as one stakeholder group. These leaders included school-based leaders, bureaucrats, community-based leaders and teacher educators preparing university graduates for Red Dirt schools. This paper focusses on what Red Dirt education leaders think is important for schooling. The findings show school leaders as ‘caught in the middle’ (Gonzalez & Firestone, 2013) between expectations from communities, and of system stakeholders who drive policy, funding and accountability measures. The paper concludes with some implications for policy and practice that follow on from the findings.